(untitled) (Italian Journal of Public Health, 2009)
Vaccines represent some of the most important tools available for the prevention of diseases. In addition to protecting the vaccinated individual from developing a potentially serious disease, they help protect the community by reducing the spread of infectious agents. Therefore, there are not only benefits for the single individual, but also advantages for the entire community and the society. This very simple consideration makes unique the public health evaluation of vaccines, with substantial differences with other public health interventions and a need to adopt different criteria to develop recommendations for use. The public health evaluation of vaccines is challenged by several factors. Vaccine randomized trials often lack adequate sample size, fail to provide critical study details, exclude important populations, and rely on proxies for important outcomes.